Розробка ефективних систем автоматизації технологічних комплексів з використанням методів сучасної теорії керування - Ладанюк, А. П.; Власенко, Л. О. (НТУ "ХПІ", 2013)
В статье рассмотрено использование сценарно-целевого подхода для анализа состояния технологического комплекса (ТК), вариантов его дальнейшего поведения при ситуациях, возникающих во время работы ТК. Представленные сценарии уточняются и раскрываются в прографах, которые являются основой для имитационного моделирования. Применение полученных результатов позволит повысить качество управления подсистемами ТК.

The usage of scenario-oriented approach for processing facility (PF) analysis, variants of its future behavior during PF operation are shown in the article. Provided scenarios are clarified and described in Prografs which are the basis for simulation. Applying of gotten results would improve control quality of the PF subsystems.
Development of effective systems for technological complexes automation with using methods of modern control theory
Keywords: системи автоматизації; інтелектуальні системи автоматизації; технологічні комплекси; харчова промисловість